2022
DOI: 10.18388/abp.2020_5679
|View full text |Cite
|
Sign up to set email alerts
|

The engineered peptide construct NCAM1-Aβ inhibits fibrillization of the human prion protein (PrP)

Abstract: In prion diseases, the prion protein (PrP) becomes misfolded and forms fibrillar aggregates that are responsible for prion infectivity and pathology. So far, no drug or treatment procedures have been approved for prion disease treatment. We have previously shown that engineered cell-penetrating peptide constructs can reduce the amount of prion aggregates in infected cells. However, the molecular mechanism underlying this effect is unknown. Here, we use atomic force microscopy (AFM) imaging to show that the amy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…All this seems to point towards a rapid co-aggregation process where large co-aggregates are formed which precipitate out of solution. Similar non-fibrillar co-aggregates were also observed for the PrP protein together with the NCAM-Aβ construct [27].…”
Section: Anti-amyloid Properties Of Signal Peptide Derived Cppssupporting
confidence: 73%
See 3 more Smart Citations
“…All this seems to point towards a rapid co-aggregation process where large co-aggregates are formed which precipitate out of solution. Similar non-fibrillar co-aggregates were also observed for the PrP protein together with the NCAM-Aβ construct [27].…”
Section: Anti-amyloid Properties Of Signal Peptide Derived Cppssupporting
confidence: 73%
“…The effect was retained, and even enhanced, upon exchanging the PrP signal peptide into the NCAM1 signal peptide [26]. A study based on AFM imaging showed that co-aggregation between our constructs and the prion protein into non-fibrillar/non-amyloid aggregates appears to be an important molecular interaction underlying these results [27]. The NCAM1 signal peptide is shorter and less hydrophobic than its PrP counterpart, which leads to higher solubility and a lower aggregation propensity.…”
Section: Anti-prion Properties Of Signal Peptide Derived Cppsmentioning
confidence: 76%
See 2 more Smart Citations
“…The aggregation of Aβ and of the human prion protein can be inhibited by certain cell-penetrating peptides (CPPs) in vitro, [37][38][39][40] which target secondary nucleation 39 and counteract the lethal damage inflicted by the Aβ peptide on neuroblastoma cells. 38 These particular CPPs contain a signal sequence for secretion and a short sequence from an amyloidogenic polypeptide: either from the prion protein or from Aβ.…”
Section: Introductionmentioning
confidence: 99%